Media Massa dalam Masyarakat Madani - Gani, Rita (Mediator, 2005)
The life of Prophet Muhammad inherited us with great values that become exemplar for society after him. Madinah Charter in the time of the Great Prophet was introduced as written rules to manage people life—through this Charter, pecially civil defense. Such norms are still relevant enough being applied in modern times. Freedom of the press in civil society translated not as absolute freedom. Censorship is still recognized in the form of norms, ethics, culture, religion, and custom-traditions among members of community. In effect, mass media in civil society aren’t free from social realities.